Results of surgical treatment in patients with local recurrences of uterine sarcomas - I. V. Matrosova; I. A. Fainshtein; I. V. Poddubnaya; M. I. Nechushkin; N. I. Lazareva; N. V. Levitskaya; V. V. Kuznetsov (Опухоли женской репродуктивной системы, 2014)
The results of treatment were studied in 95 patients with local recurrences of uterine sarcomas, who had been treated at the N.N. Blokhin Russian Cancer Research Center in 1972 to 2010. Two patient groups were comparatively analyzed after surgical and conservative (chemo- and radiotherapy) treatments. Overall survival was found to be significantly higher in the group of patients who had undergone surgical treatment.